Teaching New Keynesian Open Economy Macroeconomics at the Intermediate Level - Peter Bofinger; Eric Mayer; Timo Wollmershäuser (University of Würzburg, Department of Economics, 2006)
For the open economy the workhorse model in intermediate textbooks still is the Mundell-Fleming model, which basically extends the IS-LM model to open economy problems. The purpose of this paper is to present a simple New Keynesian model of the open economy, that introduces open economy considerations into the closed economy consensus version and that still allows for a simple and comprehensible analytical and graphical treatment. Above all, our model provides an efficient tool kit for the discussion of the costs and benefits of fixed and flexible exchange rates, which also was at the core of the Mundell-Fleming model.
Keywords: F41; E50; E10; A20; 330; open economy; inflation targeting; monetary policy rules; New Keynesian macroeconomics